CONTESTING GLOBAL FORCES THROUGH CULTURAL HYBRIDISATION:JAVANESE COVER VERSIONS OF WESTERN SONGS ON YOUTUBE (Journal of Creative Industry and Sustainable Culture, 2023)
This article examines the ways in which cover songs on YouTube using traditional language and musical instruments serve as responses to the global music industry. A band from East Java, Indonesia, Gamelawan, will serve as the case study. Gamelawan contests the global music industry by covering a number of Western songs in Javanese language and arranging the musical accompaniment for gamelan instruments. Through Qualitative Content Analysis (QCA) of selected Javanese cover versions of western songs on YouTubeby Gamelawan (Channel Gamelawan.P5Pro), this article analyses how processes of cultural reappropriation provide insights into the ways in which Indonesian musicians respond to exchanges in world culture, in general, and what Gamelawan’s works indicate about global, contemporary media usage, in particular. By utilising theconcepts of hybridisation and participatory culture, Gamelawan’s songs demonstrate that the adaptation and appropriation of outside influences through the use of technology contribute to increasing cultural diversity which, in turn, enhances stronger local identities.